2018
DOI: 10.3389/fpsyg.2018.00777
|View full text |Cite
|
Sign up to set email alerts
|

Stability of and Changes in Implicit Motives. A Narrative Review of Empirical Studies

Abstract: Although growing research indicates that certain personality traits change over the lifespan, implicit motives are often deemed to be rather stable personality characteristics. Researchers have been interested in implicit motives for several decades, but our understanding of how these dispositions change still lacks clarity. This article gives an overview and a discussion of the current evidence for the stability of and the changes in implicit motives. After elaborating on the theoretical background of the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 114 publications
0
21
0
Order By: Relevance
“…Delineation from motive dispositions -What differentiates aggregates of motivational states from explicit and implicit motives? A theoretically assumed feature of motive dispositions is a certain stability over time (see Denzinger & Brandstätter, 2018 for an overview on implicit motives). Although changes are not impossible, shifts would be assumed to occur moderately as a result of a slow situational adaptation (Bischof, 2008;Gubler & Bischof, 1991).…”
Section: Aggregated Motivational Statesmentioning
confidence: 99%
“…Delineation from motive dispositions -What differentiates aggregates of motivational states from explicit and implicit motives? A theoretically assumed feature of motive dispositions is a certain stability over time (see Denzinger & Brandstätter, 2018 for an overview on implicit motives). Although changes are not impossible, shifts would be assumed to occur moderately as a result of a slow situational adaptation (Bischof, 2008;Gubler & Bischof, 1991).…”
Section: Aggregated Motivational Statesmentioning
confidence: 99%
“…To perform these experiments, we used the Simple Transformers library which allows us to easily implement this setup. 10 As main configuration parameters, we set the max_ length parameter to 90, 11 and we re-trained the models up to two epochs. From here after, we refer as Bert-(FT) to the fine-tuned experiments.…”
Section: Simple Transformermentioning
confidence: 99%
“…The most frequently used measures of implicit motives are the Picture Story Exercise (PSE) [7], the Thematic Apperception Test (TAT) [8], the Multi-Motive Grid (MMG) [9], and the Operant Motive Test (OMT) [10,11]. Generally speaking, these tests are based on the operant methods, i.e., participants are asked ambiguous questions or are shown simple images, which they have to describe.…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence of a relationship between achievement motive and various motivational constructs, research on a relationship between achievement motive and health has been limited. The research that exists has suggested that achievement motive is associated with health benefits including the attenuation of cortisol, release of vasopressin, reduced stress, and improved immune functioning (Denzinger & Brandstatter, 2018;McClelland, 1989;McClelland et al, 1987). Furthermore, people high in achievement motivation have been found to comply with and be more involved in their medical treatment (Hatta et al, 2016) and engage in healthier behaviors such as avoiding sun exposure and lowered risk-related sexual behavior (Aspden et al, 2012) and healthier eating behaviors (Job et al, 2010).…”
Section: Achievement Motivation and Healthmentioning
confidence: 99%